Multiple Enchondromatosis: Olliers Disease- A Case Report - Sunny, George (J Clin Diagn Res, 2016)
Olliers disease is a rare disease characterized by widespread enchondromas with a unilateral predominance, in early childhood. The diagnosis is based on clinical and conventional radiological evaluations. The prognosis for olliers disease is difficult to assess. Enchondromas in olliers disease present a risk of malignant transformation into chondrosarcomas. Due to its rarity literature focusing on olliers disease is limited. This case report discusses the case of a 12-year-old female who presented with difficulty in walking, leg pain and multiple painless swellings in hands and legs for a period of 2 years.